Food Store Environment Modifies Intervention Effect on Fruit and Vegetable Intake among Low-Income Women in North Carolina - Alison A. Gustafson; Joseph Sharkey; Carmen D. Samuel-Hodge; Jessica C. Jones-Smith; Jianwen Cai; Alice S. Ammerman (Journal of Nutrition and Metabolism, 2012)
Background. The aim of the study is to determine how the food store environment modifies the effects of an intervention on diet among low-income women. Study Design. A 16-week face-to-face behavioral weight loss intervention was delivered among low income midlife women. Methods. The retail food environment for all women was characterized by (1) the number and type of food stores within census tracts; (2) availability of healthy foods in stores where participants shop; (3) an aggregate score of self-reported availability of healthy foods in neighborhood and food stores. Statistical Analyses. Multivariable linear regression was used to model the food store environment as an effect modifier between the intervention effect of fruit and vegetable serving change. Results. Among intervention participants with a low perception of availability of healthy foods in stores, the intervention effect on fruit and vegetable serving change was greater [1.89, 95% CI (0.48, 3.31)] compared to controls. Among intervention participants residing in neighborhoods with few super markets, the intervention effect on fruit and vegetable serving change was greater [1.62, 95% CI (1.27, 1.96)] compared to controls. Conclusion. Results point to how the food store environment may modify the success of an intervention on diet change among low-income women.